A novel efficient cross layer-based bandwidth reservation mechanism for next generation wireless networks. (28th August 2020) - Rajesh, G.; Krishna, P. Venkata
In this paper, a cross-layer-based efficient bandwidth reservation mechanism (CLBRM) is proposed for next generation wireless networks. Application layer and network layer are involved in the design of the cross-layer architecture. Cross-layer architecture is used to reduce the delay. Shared database is used to implement the cross-layer architecture which allows to share the information among the application layer and the network layer. Bandwidth is reserved based on the type of requests and past history of the users. Four types of requests are used in this paper and priority is assigned among these requests. Two queues are maintained for last two priority requests and pre-emption of these requests is incorporated in order to serve the highly prioritised requests in a better way. The QoS parameters like delay, throughput, blocking probability, and dropping probability are used to evaluate the performance of the proposed mechanism. The performance of the proposed mechanism, CLBRM is compared with the data driven allocation (DDA) scheme (Fan et al., 2016) and proved to perform better.